FEM MODAL ANALYSIS FOR DAMAGE DETECTION IN AIRPLANE STRUCTURES - Batista, Adson; Angelo, Francisco A.L.; Alves, Gabriela M.; Brasil, Reyolando M.L.R.F. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Technics for damage and fatigue detection has become an essential part of Aeronautic industry safety. The duration of service lives of such vehicles can be considerablyÂ extended by systematic monitoring of small, possibly undetected, damages to their structures.Â In this paper, we propose damage detection in airplane structures via modal analysis. ByÂ using Finite Element Method numerical models, developed in commercial software, as a firstÂ step, we make comparisons of the free vibration frequencies of undamaged models andÂ models where we deliberately introduce damage. We observe the difference in frequencyÂ values. In future work we will propose numerical damage indicators based on the modalÂ analysis. Keywords: Aeronautical Structure, Damage Detection, Modal Analysis, FEM.